IOT-BASED WASTE BANK APPLICATION FOR MONITORING AND MANAGING PLASTIC BOTTLES (CASE STUDY: RANCASARI WASTE BANK) - Versanika, Dayanni Vera; Aida, Riska Zafira Nurul; Aelani, Khoirida (RISTEC : Research in Information Systems and Technology, 2025)
Plastic pollution, particularly from plastic bottles, represents a significant global environmental challenge. An Internet of Things (IoT)-based waste bank application has been developed as an innovative solution to enhance the efficiency of plastic bottle waste management through real-time data monitoring. This system is designed using Wemos D1 Mini microcontroller integrated with Ultrasonic Sensors, TCRT5000 (IR) Sensors, LCD 12c, Buzzer, and the Firebase platform. Initial testing indicates that the system is capable of accurately detecting plastic bottles, with the Ultrasonic Sensor effectively identifying objects at distances less than 30 cm, while the TCRT5000 (IR) Sensor consistently counts the number of bottles passing through its detection path. Detected data is transmitted in real-time to the Firebase platform for storage and can be monitored via a mobile application. The system also successfully updates the balance on the LCD 12c display and provides notification alerts via the Buzzer each time a bottle is detected. Functional testing demonstrated a 100% success rate in bottle detection, data transmission to Firebase, and user balance updates. This system significantly improves the operational efficiency of the Rancasari Waste Bank by providing accurate and real-time data, thereby encouraging greater community participation in plastic recycling efforts. In conclusion, this application has the potential to substantially reduce plastic waste accumulation and contribute to more sustainable environmental management.